2012
DOI: 10.4012/dmj.2012-058
|View full text |Cite
|
Sign up to set email alerts
|

Toughening of CAD/CAM all-ceramic crowns by staining slurry

Abstract: The ability of staining slurries containing silver and/or potassium compounds to enhance the mechanical properties of a leucitereinforced glass ceramic (IPS Empress CAD) was investigated by measuring the Vickers hardness, median crack length, toughness, and compressive residual stress of specimens. A staining slurry containing potassium ions was found to increase the toughness of IPS specimens more than a staining slurry containing only silver ions when applied prior to sintering. None of the staining slurries… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…Higher survival rates and estimated lifetimes for e.max CAD onlays and inlays in comparison to those fabricated out of Empress CAD probably reflect their differences in mechanical properties. Flexural strength and fracture toughness of Empress CAD have been measured to means of 137.5 ± 23.3 MPa (Charlton et al 2008) and 1.4 ± 0.07 MPa√m (Uno et al 2012), respectively, while the same properties for e.max CAD show 2 times these values (Pollington and van Noort 2012). Leucite, the crystal phase of Empress CAD, is not very effective in promoting crack deflection (Apel et al 2008), a toughening mechanism common in lithium disilicate glass-ceramics (Lohbauer, Müller, et al 2008;Dittmer et al 2014;Belli et al 2015), but also, the high glass phase content (~60 vol% in Empress CAD) plays an important role.…”
Section: Discussionmentioning
confidence: 99%
“…Higher survival rates and estimated lifetimes for e.max CAD onlays and inlays in comparison to those fabricated out of Empress CAD probably reflect their differences in mechanical properties. Flexural strength and fracture toughness of Empress CAD have been measured to means of 137.5 ± 23.3 MPa (Charlton et al 2008) and 1.4 ± 0.07 MPa√m (Uno et al 2012), respectively, while the same properties for e.max CAD show 2 times these values (Pollington and van Noort 2012). Leucite, the crystal phase of Empress CAD, is not very effective in promoting crack deflection (Apel et al 2008), a toughening mechanism common in lithium disilicate glass-ceramics (Lohbauer, Müller, et al 2008;Dittmer et al 2014;Belli et al 2015), but also, the high glass phase content (~60 vol% in Empress CAD) plays an important role.…”
Section: Discussionmentioning
confidence: 99%
“…They compared the effects of silver nanoparticles and silver hydroxyapatite nanoparticles on color and fracture strength of dental ceramic, where similar conclusions were elicited; incorporation of silver nanoparticles increased the fracture strength of dental ceramics, whereas incorporation of silver hydroxyapatite nanoparticles decreased the fracture strength of dental ceramic and both nanoparticles affected the color properties adversely, limiting the concentration of silver nanoparticles to 2 wt%. Uno et al 1 and Fujieda et al 15 reported improved fracture resistance after incorporation of silver nanoparticles. The investigation showed greater susceptibility to corrosion resistance and coefficient of thermal expansion.…”
Section: Discussionmentioning
confidence: 99%
“…8-10 Various nanoparticles such as silver oxide (AgO), 11 zirconia (ZrO 2 ), 12 alumina (Al 2 O 3 ), 14 hydroxyapatite (HA), 11 titanium dioxide (TiO 2 ) 13 and platinum (Pt) 15 have been tried in different proportions to improve the properties of feldspathic porcelain. 11-15 Uno et al, 1 Mohsen et al, 11 Esparza-Vázquez et al, 13 Fujieda et al 15 and Siegel et al 16 have determined the fracture toughness with various nanoparticles. The results from these studies were supportive but still prospects exist in improving the properties of feldspathic porcelain.…”
Section: Introductionmentioning
confidence: 99%
“…Fujieda et al proved that fracture toughness and Young's modulus increased with addition of AgNPs and Pt-NPs [146]. Another study showed that the addition of silver ions improved mechanical properties of Computer Aided Design/Computer Aided Manufacturing (CAD/CAM) blocks and at the same time, decreased crack length [147]. Mohsen et al examined the effect of AgNPs on the color of ceramics.…”
Section: Prostheticmentioning
confidence: 99%